A casting material for resisting metal ion corrosion

By using wollastonite, barium sulfate and magnesium aluminum spinel in the castable, the barium feldspar phase and magnesium aluminum spinel are formed, which solves the problem of metal ion erosion and achieves the efficient corrosion resistance and long-term resistance of the castable use.

CN119191858BActive Publication Date: 2025-02-18SHANDONG LUMING NEW MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411707872.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-18
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

During the smelting of aluminum and its alloys, metal ions such as aluminum ions, calcium ions, sodium ions, etc. are prone to erode the castable material and affect product quality.

Method used

Wollastonite, barium sulfate and magnesium aluminum spinel are used as mineral auxiliary materials to generate barium feldspar phase through sintering and composite, which reduces the reactivity of the castable material, and uses the barrier effect of magnesium aluminum spinel to enhance the resistance to metal ion erosion. .

Benefits of technology

Effectively resist the erosion of metal ions, improve the service life of castables, and is suitable for the process of making aluminum by melting method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of amorphous refractory materials, and specifically discloses a castable for resisting metal ion corrosion. The present application selects wollastonite, barium sulfate and magnesium aluminum spinel as components of mineral auxiliary materials. Barium sulfate can be sintered and compounded with the mullite phase formed in the castable, and produce a barium feldspar phase. Under the synergistic effect of magnesium aluminum spinel and barium feldspar phase, it is more difficult for metal ions such as aluminum ions, calcium ions, sodium ions, magnesium ions, iron ions, ferrous ions, manganese ions, and copper ions to react with the castable. Therefore, the castable of the present application can fully resist the corrosion of metal ions, has a long service life, and is suitable for use in the process of molten aluminum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of amorphous refractory materials, and more particularly to a castable material for resisting metal ion corrosion. Background Art

[0002] The melting method is a production process for remelting electrolytic aluminum and scrap aluminum to obtain machinable aluminum. It has a low production cost and is a good way to fully utilize aluminum resources. The reason why the aluminum melting furnace used in the melting method can work at high temperatures is inseparable from the protection of high-temperature resistant furnace lining materials. With the development of the scale of my country's aluminum industry and technological progress, the number of aluminum processing companies has continued to increase, and aluminum melting furnaces have also been continuously enlarged. These changes have put forward higher and newer requirements for refractory materials used in aluminum melting furnaces.

[0003] In the related technology, there is a non-stick aluminum castable, which is prepared from the following raw materials: 65-67wt% high-alumina aggregate, 10-12wt% high-alumina fine powder, 4-6wt% calcined α-alumina fine powder, 3-5wt% expansion agent, 3-4wt% wollastonite powder, 4-5wt% flow agent, 5-7wt% aluminate cement, and also includes a water reducer equivalent to 0.2-0.3% of the total mass of the above components; the high-alumina aggregate is high-alumina bauxite clinker; the high-alumina fine powder is high-alumina bauxite clinker fine powder; the expansion agent is kyanite; the flow agent is silica fume; and the water reducer is a polycarboxylic acid water reducer.

[0004] Regarding the above-mentioned related technology, the inventor believes that although this technology improves the strength of the castable to a certain extent, when smelting aluminum and its alloys, metal ions such as aluminum ions, calcium ions, sodium ions, magnesium ions, iron ions, ferrous ions, manganese ions, and copper ions in the aluminum alloy are still easy to invade the castable, causing erosion of the castable and easily affecting the product quality of aluminum and its alloys. Summary of the invention

[0005] In the related art, when smelting aluminum and its alloys, aluminum ions, calcium ions, sodium ions, magnesium ions, iron ions, ferrous ions, manganese ions, copper ions and other metal ions in the aluminum alloy are still easy to invade the castable, causing corrosion of the castable, which is easy to affect the product quality of aluminum and its alloys. In order to improve this defect, the present application provides a castable for resisting metal ion corrosion.

[0006] The present application provides a castable for resisting metal ion corrosion, which adopts the following technical solution:

[0007] A castable for resisting metal ion corrosion, the castable comprising a base material and an admixture, the admixture comprising a water reducer, the base material comprising the following components: 4-6wt% alumina powder, 1.5-2.5wt% silica fume, 3-5wt% expansion agent, 8-14wt% mineral auxiliary material, 5-7wt% aluminate cement, the balance being supplemented to 100wt% by aluminum materials; the aluminum materials comprising high-alumina bauxite clinker, the mineral auxiliary materials comprising wollastonite, barium sulfate and magnesium aluminum spinel.

[0008] By adopting the above technical scheme, the present application selects wollastonite, barium sulfate and magnesium aluminum spinel as components of mineral auxiliary materials. Magnesium aluminum spinel is an isotropic octahedral structure. The Al-O and Mg-O of magnesium aluminum spinel are bonded by ionic bonds. The strength of their electrostatic bonds is the same and the structural stability is relatively high. This crystal structure enables MA crystals to have excellent thermal shock stability, high temperature resistance and ideal resistance to metal ion corrosion, and has a good barrier effect. In the present application, wollastonite, alumina powder, silica fume and aluminum materials can produce mullite phase after being smelted together, and barium sulfate can be sintered and compounded with the mullite phase in the castable to produce barium feldspar phase. The formation of barium feldspar phase consumes the mullite phase and highly reactive silicon dioxide in the castable, reducing the reactivity of the castable. The formation of the celsium feldspar phase is also accompanied by a barium-rich liquid phase, which can reduce the pores inside and on the surface of the castable, and can also fill the structural defects of the magnesium-aluminum spinel itself and the expansion cracks formed under high temperature conditions, so that the barrier effect of the magnesium-aluminum spinel can be more fully exerted. Under the synergistic effect of the magnesium-aluminum spinel and the celsium feldspar phase, it is more difficult for metal ions such as aluminum ions, calcium ions, sodium ions, magnesium ions, iron ions, ferrous ions, manganese ions, and copper ions to react with the castable. Therefore, the castable of the present application can fully resist the erosion of metal ions, has a long service life, and is suitable for use in the process of molten aluminum.

[0009] Preferably, the aluminate cement is prepared according to the following method:

[0010] (1) industrial alumina and natural dolomite are mixed, the mixture is ball-milled using a ball mill, and then the ball-milled product is pressed into a green body using a press for standby use;

[0011] (2) The green body is dried and then calcined. After the calcination, the calcined product is crushed and then ground to obtain aluminate cement.

[0012] By adopting the above technical scheme, the present application uses industrial alumina and natural dolomite as raw materials. During the calcination process, the decomposition reaction of dolomite first occurs in the range of 700-900°C to generate calcium oxide and magnesium oxide. Then, above 1000°C, calcium oxide reacts with alumina to produce calcium aluminate and calcium dialumate, and magnesium oxide reacts with alumina to produce magnesium aluminum spinel, and finally aluminate cement containing magnesium aluminum spinel is obtained. By using this aluminate cement, the total content of magnesium aluminum spinel in the castable can be increased, which helps to give full play to the synergistic effect of magnesium aluminum spinel and barium feldspar phase, thereby helping to improve the castable's resistance to metal ion corrosion.

[0013] Preferably, the weight ratio of barium sulfate to magnesium aluminum spinel is 1:(2.0-2.1).

[0014] By adopting the above technical solution, the present application optimizes the weight ratio of barium sulfate and magnesium aluminum spinel, which helps to fully improve the castable's resistance to metal ion corrosion.

[0015] Preferably, the weight ratio of the barium sulfate to wollastonite powder is 1:(0.6-1.1).

[0016] By adopting the above technical solution, the present application optimizes the weight ratio of barium sulfate and wollastonite powder, which helps to fully improve the castable's resistance to metal ion corrosion.

[0017] Preferably, the expansion agent comprises kyanite and magnesia.

[0018] By adopting the above technical solution, the present application adopts magnesia and kyanite as expansion agents. Since the expansion peak temperatures of these two minerals are around 1400°C and 1300°C respectively, the expansion of the two will occur successively, reducing the concentration of expansion pressure, which helps to reduce the structural defects generated during the casting process. In addition, after sintering magnesia and high-alumina bauxite clinker in aluminum materials together, magnesia-alumina spinel will be produced, which increases the total content of magnesia-alumina spinel in the castable, so that the synergistic effect between magnesia-alumina spinel and celsium feldspar phase can be more fully exerted, thereby helping to improve the castable's resistance to metal ion corrosion.

[0019] Preferably, the mineral auxiliary material also includes magnesium fluoride.

[0020] By adopting the above technical solution, magnesium fluoride can promote the formation of magnesium-aluminum spinel, which helps to improve the castable's resistance to metal ion corrosion.

[0021] Preferably, the aluminum material also includes andalusite.

[0022] By adopting the above technical solution, the quartz glass phase in the andalusite can soften during the sintering process, thereby absorbing part of the stress generated by the thermal expansion of the castable, and can fill the structural defects, which helps to reduce the penetration of aluminum liquid and improve the castable's resistance to metal ion corrosion.

[0023] Preferably, the weight of the andalusite accounts for 5-10% of the total weight of the aluminum material.

[0024] By adopting the above technical solution, the present application optimizes the dosage range of andalusite, which helps to improve the castable's resistance to metal ion corrosion.

[0025] Preferably, the mineral auxiliary material also includes silicon carbide powder.

[0026] By adopting the above technical solution, the surface of silicon carbide powder can be oxidized under high temperature conditions to produce highly active silicon dioxide. Highly active silicon dioxide can participate in the sintering process of the castable and react with alumina to form a mullite phase, thereby promoting the improvement of the degree of mullitization in the castable. Due to the increase in the total amount of mullite phase, the sintering composite of mullite phase and barium sulfate is more thorough, and more celsium feldspar phase and associated barium-rich liquid phase can be generated, which helps to improve the castable's resistance to metal ion corrosion.

[0027] Preferably, the mineral auxiliary material further comprises mullite whiskers, and the mullite whiskers are prepared according to the following method:

[0028] Andalusite sericite phyllite, ammonium aluminum sulfate and sodium dihydrogen phosphate are mixed, anhydrous ethanol is added to the mixture and then ball-milled and dispersed, the ball-milled product is dried and ground, and then pressed into a green body, the green body is dried and calcined, and then pickled in a hydrofluoric acid solution, and after the pickling is completed, it is washed with water and dried to obtain mullite whiskers.

[0029] By adopting the above technical solution, the addition of mullite whiskers increases the total amount of mullite phase in the castable, promotes the sintering and compounding of mullite phase and barium sulfate, and is conducive to the synergistic effect of magnesium aluminum spinel and barium feldspar phase. At the same time, mullite whiskers can also reinforce the castable through their own good mechanical properties. Therefore, the castable with the addition of mullite whiskers is not easy to peel off after molding, and is not easy to have structural defects during the aluminum liquid erosion process, which helps to improve the castable's resistance to metal ion erosion.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. This application uses wollastonite, barium sulfate and magnesium aluminum spinel as components of mineral auxiliary materials. Barium sulfate can be sintered and compounded with the mullite phase formed in the castable to produce barium feldspar phase. Under the synergistic effect of magnesium aluminum spinel and barium feldspar phase, it is more difficult for metal ions such as aluminum ions, calcium ions, sodium ions, magnesium ions, iron ions, ferrous ions, manganese ions, and copper ions to react with the castable. Therefore, the castable of this application can fully resist the erosion of metal ions, has a long service life, and is suitable for application in the process of molten aluminum.

[0032] 2. The present application uses industrial alumina and natural dolomite as raw materials to prepare aluminate cement containing magnesia-alumina spinel. By using this aluminate cement, the total content of magnesia-alumina spinel in the castable can be increased, thereby helping to improve the castable's resistance to metal ion corrosion. DETAILED DESCRIPTION

[0033] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0034] The following is an explanation using Preparation Example 1.

[0035] Preparation Example 1

[0036] In this preparation example, aluminate cement was prepared according to the following method:

[0037] (1) 140 mesh industrial alumina and 200 mesh natural dolomite were mixed in a weight ratio of 45:55, and the mixture was ball-milled for 30 min using a φ305 mm×305 mm ball mill. Then, the ball-milled product was pressed into a green body at a pressure of 60 MPa using a press for standby use;

[0038] (2) The green body is dried at 110°C for 24 hours and then calcined at 1450°C for 3 hours. After the calcination, the calcined product is crushed and ground to obtain aluminate cement.

[0039] The following is an explanation using Preparation Example 2.

[0040] Preparation Example 2

[0041] In this preparation example, mullite whiskers were prepared according to the following method:

[0042] Andalusite sericite phyllite, ammonium aluminum sulfate dodecahydrate, and sodium dihydrogen phosphate were mixed in a molar ratio of 10:5.48:0.31, and 0.2% of

[0043] The product was dispersed by ball milling after being dried in anhydrous ethanol, and then ground. Particles with a particle size of less than 0.075 mm were screened out and pressed into a green body. The green body was dried at 110°C for 24 hours, then calcined at 1400°C for 6 hours, and then pickled in a 40wt% hydrofluoric acid solution at 50°C for 5 hours. After the pickling, it was washed with water and dried to obtain mullite whiskers.

[0044] Examples 1-5

[0045] The following description is given by taking Example 1 as an example.

[0046] Example 1

[0047] In this embodiment, the aluminum material is high-alumina bauxite clinker; the alumina content of the high-alumina bauxite clinker is 80wt%, and the high-alumina bauxite clinker is composed of five graded materials of 5-8mm, 3-5mm, 1-3mm, 0.075mm-1mm, and 200 mesh in sequence according to the weight ratio of 3:4:4:2.4:2; the mineral auxiliary materials are composed of wollastonite, barium sulfate and magnesium aluminum spinel, the weight ratio of barium sulfate to magnesium aluminum spinel is 1:1.9, the weight ratio of barium sulfate to wollastonite powder is 1:0.3, and the particle size of the mineral auxiliary materials is 100 mesh; the expansion agent is kyanite, and the particle size of the expansion agent is 80 mesh; the specific surface area of ​​silica fume is 15000m 2 / kg; the type of alumina powder is calcined α alumina (1000 mesh); the aluminate cement is CA90 pure aluminate cement.

[0048] This embodiment provides a castable for resisting metal ion corrosion, the castable components include a base material and an admixture, the admixture is a polycarboxylate water reducer with a water reduction rate of 27%, and the amount of the admixture is 0.2% of the total weight of the base material. The base material includes the following components: 4wt% alumina powder, 1.5wt% silica fume, 3wt% expansion agent, 8wt% mineral auxiliary material, 5wt% aluminate cement, and the balance is supplemented by aluminum materials to 100wt%.

[0049] As shown in Table 1, the differences between Examples 1-5 are mainly in the different base material ratios in the castables.

[0050] Table 1 Base material ratio in castable

[0051]

[0052] Example 6

[0053] The difference between this embodiment and embodiment 5 is that aluminate cement is prepared according to the method of preparation example 1.

[0054] As shown in Table 2, the difference between Examples 6-9 is that the weight ratio of barium sulfate to magnesium aluminum spinel (referred to as the first ingredient ratio) is different.

[0055] Table 2 First ingredient ratio

[0056]

[0057] As shown in Table 3, the difference between Examples 9-12 is that the weight ratio of barium sulfate to wollastonite powder (referred to as the second ingredient ratio) is different.

[0058] Table 3 Second ingredient ratio

[0059]

[0060] Embodiment 13

[0061] The difference between this embodiment and embodiment 12 is that the expansion agent is mixed with kyanite and magnesia in a weight ratio of 1:2, the particle size of the magnesia is 120 mesh, the mass fraction of magnesium oxide in the magnesia is 97.2%, the mass fraction of iron oxide is 1.4%, the mass fraction of calcium oxide is 0.6%, and the mass fraction of silicon dioxide is 0.4%.

[0062] Embodiment 14

[0063] The difference between this embodiment and Embodiment 13 is that the mineral auxiliary material further includes magnesium fluoride, and the weight ratio of barium sulfate to magnesium fluoride is 1:0.2.

[0064] Embodiment 15

[0065] The difference between this embodiment and embodiment 14 is that the aluminum material also includes andalusite, and the weight of andalusite accounts for 3% of the total weight of the aluminum material, and the remainder is high-alumina clinker.

[0066] As shown in Table 4, the difference between Examples 15-18 is that the percentage of the weight of andalusite to the total weight of the aluminum material (referred to as andalusite percentage) is different.

[0067] Table 4 The weight of andalusite as a percentage of the total weight of aluminum materials

[0068]

[0069] Embodiment 19

[0070] The difference between this embodiment and Embodiment 18 is that the mineral auxiliary material also includes silicon carbide powder, and the weight ratio of barium sulfate to silicon carbide powder is 1:0.3.

[0071] Embodiment 20

[0072] The difference between this embodiment and Embodiment 19 is that the mineral auxiliary material further includes mullite whiskers, and the mullite whiskers are prepared according to the method of Preparation Example 2, and the weight ratio of barium sulfate to mullite whiskers is 1:0.1.

[0073] Comparative Example 1

[0074] In this comparative example, the high-alumina aggregate is high-alumina bauxite clinker with an alumina content of 80wt%, and the high-alumina aggregate is composed of four graded materials of 5-8mm, 3-5mm, 1-3mm, and 0.075mm-1mm in sequence according to a weight ratio of 3:4:4:2.4. The high-alumina fine powder is high-alumina bauxite clinker fine powder with an alumina content of 80wt%, and the particle size of the high-alumina fine powder is 200 mesh; the particle size of the calcined α-alumina is 1000 mesh, the expansion agent is 80 mesh kyanite, the particle size of the wollastonite powder is 100 mesh, and the flow agent is a specific surface area of ​​15000m 2 / kg of silica fume, and the aluminate cement is CA90 pure aluminate cement.

[0075] The comparative example provides a non-stick aluminum castable, which is prepared from the following raw materials: 67wt% high-alumina aggregate, 10wt% high-alumina fine powder, 6wt% calcined α-alumina micropowder, 3wt% expansion agent, 4wt% wollastonite powder, 5wt% flow agent, 5wt% aluminate cement, and also includes a high-efficiency water reducer equivalent to 0.2% of the total mass of the above components; the high-alumina aggregate is high-alumina bauxite clinker; the high-alumina fine powder is high-alumina bauxite clinker fine powder; the expansion agent is kyanite; the flow agent is silicon micropowder; and the high-efficiency water reducer is a polycarboxylate water reducer.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that the mineral auxiliary material does not include barium sulfate.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 is that the mineral auxiliary material does not include magnesium aluminum spinel.

[0080] The materials were weighed according to the formulas recorded in the examples and comparative examples, and the materials were added to the drum mill for premixing for 1 hour, and then stirred in a forced mixer for 90 seconds. The admixture (water reducer) was added to the water and added to the forced mixer, and the mixture was added to the mold for molding after continued stirring for 3 minutes. After 24 hours of mold curing, the mold was demolded, and then cured at room temperature for 24 hours. The green body was placed in a drying oven and dried at 110°C for 24 hours, and then heated to 900°C for 1 hour, then heated to 1200°C for 1 hour, and then heated to 1400°C for 0.5 hours, and then cooled with the furnace to obtain a crucible sample.

[0081] 6063# aluminum alloy was used as the corrosive medium for the corrosion resistance test, and its chemical composition is shown in Table 5.

[0082] Table 5 Chemical composition of 6063# aluminum alloy (wt%)

[0083]

[0084] The crucible samples prepared from the castables of each embodiment and comparative example were used as the test object, and the erosion rate was tested by the static crucible method described in GB / T 8931-2007 Test Method for Slag Resistance of Refractory Materials. The test temperature and holding time were 850°C × 72h. After the test results were obtained, the ratio between the erosion rate of each embodiment and comparative example and the erosion rate of comparative example 1 was calculated based on the erosion rate measured in comparative example 1, and the ratio was recorded as the relative erosion rate. The results are shown in Table 6.

[0085] Table 6 Relative erosion rate

[0086]

[0087] Combining Examples 1-5 and Comparative Example 1 and Table 6, it can be seen that the relative erosion rates measured in Examples 1-5 are all lower than those in Comparative Example 1, indicating that when wollastonite, barium sulfate and magnesium aluminum spinel are selected as components of mineral auxiliary materials, the castable has a strong resistance to the erosion of molten aluminum and is suitable for long-term application in the process of molten aluminum.

[0088] Combining Example 1 and Comparative Examples 2-3 with Table 6, it can be seen that when wollastonite is not used together with barium sulfate and magnesium aluminum spinel, the castable has limited ability to resist aluminum liquid corrosion, and a larger area of ​​corrosion occurs.

[0089] Combining Example 5 and Example 6 and Table 6, it can be seen that the relative erosion rate measured in Example 6 is lower. This is because the aluminate cement in Example 6 contains magnesia-alumina spinel, which can increase the total amount of magnesia-alumina spinel in the castable, thereby improving the castable's resistance to metal ion corrosion.

[0090] It can be seen from Examples 6-9, Examples 9-12 and Table 6 that when the weight ratio of barium sulfate to magnesium aluminum spinel is 1:(2.0-2.1), and the weight ratio of barium sulfate to wollastonite powder is 1:(0.6-1.1), the castable has good resistance to metal ion corrosion.

[0091] Combining Example 12, Example 13 and Table 6, it can be seen that the relative erosion rate measured in Example 13 is lower. This is because magnesia-alumina spinel is produced after sintering magnesia sand and high-alumina bauxite clinker in the aluminum material, which increases the total content of magnesia-alumina spinel in the castable, and helps to improve the castable's resistance to metal ion corrosion.

[0092] Combining Example 13, Example 14 and Table 6, it can be seen that the relative erosion rate measured in Example 14 is lower. This is because magnesium fluoride can promote the formation of magnesium aluminum spinel, which helps to improve the castable's resistance to metal ion corrosion.

[0093] Combining Example 14, Examples 15-18 and Table 6, it can be seen that the relative erosion rate measured in Examples 15-18 is relatively low. This is because the quartz glass phase in andalusite can soften during the sintering process, thereby absorbing part of the stress generated by the thermal expansion of the castable, and can fill the structural defects, which helps to reduce the penetration of aluminum liquid and improve the castable's resistance to metal ion corrosion. In Examples 15-18, the relative erosion rate measured in Examples 16-18 is lower than that in Example 15, indicating that when the weight of andalusite accounts for 5-10% of the total weight of the aluminum material, it helps to improve the castable's resistance to metal ion corrosion.

[0094] It can be seen from Example 18 and Example 19 and Table 6 that the relative erosion rate measured in Example 19 is lower. This is because the silicon carbide powder can promote the improvement of the degree of mullite in the castable, promote the sintering and compounding of the mullite phase and barium sulfate, and help improve the castable's resistance to metal ion corrosion.

[0095] It can be seen from Example 19, Example 20 and Table 6 that the relative erosion rate measured in Example 20 is lower. This is because the mullite whiskers can be sintered and composited with barium sulfate, and at the same time, the castable is not easy to peel off after molding, which hinders the occurrence of structural defects during the aluminum liquid erosion process and helps to improve the castable's resistance to metal ion corrosion.

[0096] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A castable for resisting metal ion corrosion, characterized in that: The components of the castable include a base material and an admixture, wherein the admixture includes a water reducer, and the base material includes the following components: 4-6wt% alumina powder, 1.5-2.5wt% silica fume, 3-5wt% expansion agent, 8-14wt% mineral auxiliary materials, 5-7wt% aluminate cement, and the balance is supplemented by aluminum materials to 100wt%; the aluminum material includes high-alumina bauxite clinker, and the mineral auxiliary materials include magnesium fluoride, wollastonite, barium sulfate and magnesium aluminum spinel; the weight ratio of the barium sulfate to magnesium aluminum spinel is 1:(2.0-2.1); the weight ratio of the barium sulfate to wollastonite powder is 1:(0.6-1.1); the expansion agent includes kyanite and magnesia sand; The aluminate cement is prepared according to the following method: (1) industrial alumina and natural dolomite are mixed, the mixture is ball-milled using a ball mill, and then the ball-milled product is pressed into a green body using a press for standby use; (2) The green body is dried and then calcined. After the calcination, the calcined product is crushed and then ground to obtain aluminate cement.

2. The castable material for resisting metal ion corrosion according to claim 1, characterized in that: The aluminum material also includes andalusite.

3. The castable material for resisting metal ion corrosion according to claim 2, characterized in that: The weight of the andalusite accounts for 5-10% of the total weight of the aluminum material.

4. The castable material for resisting metal ion corrosion according to claim 2, characterized in that: The mineral auxiliary materials also include silicon carbide powder.

5. The castable material for resisting metal ion corrosion according to claim 2, characterized in that: The mineral auxiliary material also includes mullite whiskers, and the mullite whiskers are prepared according to the following method: Andalusite sericite phyllite, ammonium aluminum sulfate and sodium dihydrogen phosphate are mixed, anhydrous ethanol is added to the mixture and then ball-milled and dispersed, the ball-milled product is dried and ground, and then pressed into a green body, the green body is dried and calcined, and then pickled in a hydrofluoric acid solution, and after the pickling is completed, it is washed with water and dried to obtain mullite whiskers.

Citation Information

Patent Citations

  • Method for preparing magnesia-alumina spinel-containing aluminate cement

    CN101891408A

  • Non-stick aluminum castable and preparation method thereof

    CN117383912A